A genome-wide association analysis for susceptibility of pigs to enterotoxigenic Escherichia coli F41. (3rd March 2016) - Ji, H. Y.; Yang, B.; Zhang, Z. Y.; Ouyang, J.; Yang, M.; Zhang, X. F.; Zhang, W. C.; Su, Y.; Zhao, K. W.; Xiao, S. J.; Yan, X. M.; Ren, J.; et al.
Abstract : Enterotoxigenic Escherichia coli (ETEC) is a type of pathogenic bacteria that cause diarrhea in piglets through colonizing pig small intestine epithelial cells by their surface fimbriae. Different fimbriae type of ETEC including F4, F18, K99 and F41 have been isolated from diarrheal pigs. In this study, we performed a genome-wide association study to map the loci associated with the susceptibility of pigs to ETEC F41 using 39454 single nucleotide polymorphisms (SNPs) in 667 F2 pigs from a White Duroc×Erhualian F2 cross. The most significant SNP (ALGA0022658, P =5.59×10 −13 ) located at 6.95 Mb on chromosome 4. ALGA0022658 was in high linkage disequilibrium ( r 2 >0.5) with surrounding SNPs that span a 1.21 Mb interval. Within this 1.21 Mb region, we investigated ZFAT as a positional candidate gene. We re-sequenced cDNA of ZFAT in four pigs with different susceptibility phenotypes, and identified seven coding variants. We genotyped these seven variants in 287 unrelated pigs from 15 diverse breeds that were measured with ETEC F41 susceptibility phenotype. Five variants showed nominal significant association ( P <0.05) with ETEC F41 susceptibility phenotype in International commercial pigs. This study provided refined region associated with susceptibility of pigs to ETEC F41 than that reported previously. Further works are needed to uncover the underlying causal mutation(s).